PESONA BAHASA ASING DI MENU LOKAL: DAMPAKNYA PADA PILIHAN KULINER WISATAWAN - Firdaus, Ahmad Yusuf; Novitasari, Nine Febrie; Ardiansyah, Supriyanto (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
To enhance the culinary experience, good menu translation is essential, especially in culturally diverse areas. This study analyzes how tourists' preferences for two restaurants in Situbondo, Arabian Lounge and Denta Café, are influenced by the readability of their menu translations. The research provides insights into individual decision-making processes by applying the Readability Theory to evaluate the clarity of translated menus and the Preference Theory to understand how readability affects tourists' food choices. Primary data was collected through surveys assessing menu readability and tourists' food preferences, while secondary data was obtained from relevant literature. The framework by Nababan et al. (2012) was used to evaluate readability, and the tool by Dyer & Jia (2001) was applied to assess visitors' preferences. The results show a strong positive correlation between readability and preferences for main dishes, snacks, and beverages. For main dishes, 85.2% showed high readability, and 92.6% were selected by tourists; for snacks, the same occurred with 80%. With the highest readability rate (95%) and preference rate (92.5%), beverages demonstrated the importance of clarity in helping customers make decisions. These results highlight the need for restaurant owners to prioritize easily readable menu descriptions to satisfy and engage customers.